The Value of Ammonia as a Biomarker in Patients with Cirrhosis - Ballester, Maria Pilar; Durmazer, Esra Nur; Qi, Tingting; Jalan, Rajiv (Seminars in Liver Disease, 2024)
Ammonia is a product of amino acid metabolism that accumulates in the blood of patients with cirrhosis and plays a pivotal role in the pathogenesis of hepatic encephalopathy (HE). Despite being one of the main drivers of brain dysfunction, for many years international societies stated that increased blood ammonia does not add any diagnostic, staging, or prognostic value for HE in patients with cirrhosis. Nonetheless, in the last decades, evidence is emerging that supports the utility of ammonia for risk stratification, but its role in guiding HE diagnosis, staging, and treatment is unclear and there is equipoise in its use in clinical practice. This review provides the latest evidence on the value of ammonia as a biomarker in patients with cirrhosis. Although correct measurement of ammonia requires disciplined sample collection, it provides extremely useful clinical guidance for the diagnosis of HE, offers prognostic information, and it defines a therapeutic target.
Keywords: ammonia; hepatic encephalopathy; cirrhosis; biomarker